Декоративні верби колекції національного ботанічного саду ім. М.М. Гришка НАН України, їх шкідники та заходи із захисту - Gromova, O.P.; Gorelov, O.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The biological and ecological characteristics of some ornamental willows collection of M.M. Gryshko National Botanical Garden of the NAS of Ukraine are given. The composition of pests, their biology and protection measures are described.